The Role of Reed-Sternberg CD30 Receptor and Lymphocytes in Pathogenesis of Disease and Its Implication for Treatment - Ikhwan Rinaldi (Acta Medica Indonesiana, 2018)
Hodgkin lymphoma is a cancer that can be cured using standard chemotherapy with or without radiation. Although it accounts for only 0.6% of all malignancy worldwide, but it usually affects young adults with median age of 38 years. About 60 to 90% cases can be cured depending on its stage and 5 to 10% cases are refractory to the first-line chemotherapy; while 20 to 30% patients experiencing relapse after receiving the first-line chemotherapy. The relapse causes new problem in treatment. A monoclonal antibody-chemotherapy conjugate, Brentuximab vedotin, was approved by Food Drug Association and European Medicine since 2011 dan was approved by European Medicine Agency since 2012 to treat relapsed classical Hodgkin lymphoma and anaplastic large cell lymphoma (ALCL). Brentuximab vedotin has also been known as anti-CD30.